General chemistry : the essential concepts - Chang, Raymond (McGraw-Hill Education, 2014)
Presenting only the material that is essential for a one-year general chemistry course, this book incorporates real-world examples; helping students visualize the three-dimensional atomic and molecular structures that are the basis of chemical activity; and developing problem-solving and critical thinking skills.